PELATIHAN PELAKSANAAN PERSONAL HEALTH RECORD (PHR) PADA PASIEN DENGAN HIPERTENSI DI PUSKESMAS KAHURIPAN TASIKMALAYA TAHUN 2023 - Setiadi, Dedi; Suryani Kurniasih, Dewi Lena Suryani; Fadly, Fery (Edukasi Masyarakat Sehat Sejahtera (EMaSS) : Jurnal Pengabdian kepada Masyarakat, 2024)
The Silent Killer" is a term used for Hypertension or high blood pressure, as it often occurs without symptoms. Hypertension can be diagnosed with a blood pressure reading of ≥140 mmHg and/or ≥90 mmHg. Hypertension is the leading single contributor to heart disease, kidney failure, and stroke in Indonesia (Ministry of Health, RI, 2021). According to data from the Health Office of Tasikmalaya City, the highest incidence of hypertension occurs in the Tamansari Primary Health Care service area, totaling 2,494 cases, with 1,593 cases among females. It is estimated that only one-third of hypertension cases in Indonesia are diagnosed, with the rest going undetected. In the era of paper-based medical records, the disciplines of Medical Records and Health Information (RMIK) and medical, clinical, and/or health informatics are usually quite separate, each focusing on different aspects, although they complement each other in domains and skills. The objective of this activity is to encourage the community to use Personal Health Records (PHR) for hypertension patients in the city of Tasikmalaya. The method involves training 20 Posbindu cadres responsible for hypertension data management, with the participation of 4 students. The results show an increase in understanding by 1.5%, as indicated by the improvement from pre-test to post-test results (Good 15%, Very Good 35%). Up-to-date information about the importance of personal health records is crucial, and it is recommended that community health centers actively appreciate Posbindu cadres to motivate them to successfully implement manual PHRs for hypertension patients.